Sosialisasi Bahaya Penggunaan Narkoba Bagi Generasi Milenial Di SMP Negeri 11 Ambon - Laury M. Ch. Huwae; Stela Salamor; Sri J. A. Bandu; Karan Silaratubun; Hubert A. Mainake; Ronald D. Hukubun (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2022)
Drugs are one of society's diseases that are growing very rapidly and are difficult to eradicate. The main target of the largest distribution and use is dominated by the younger generation while the younger generation is the backbone and driver of change for the Indonesian nation. Formation of morals and ethics from an early age is the first step as an effort to prevent drug use, so that in real work lectures in Amahusu Village students run a program namely socialization of the dangers of drug use for the millennial generation. The purpose of this program is to shape the character of students by introducing caused by drug use. This activity was carried out on November 15 2022 located at SMP Negeri 11 Ambon. The implementation method uses lecture and sharing methods. With this activity, it is hoped that students will not only know the dangers but can fight drugs for the sake of creating a healthy life, a harmonious family and a bright future.